Shockwaves in consumer minds: The thunderous role of media in sculpting brand popularity - Fitrianna, Hafizh (Asian Management and Business Review, 2024)
This study explores the complex relationship between brand popularity, media exposure, curiosity, fear of missing out, and consumers’ information-seeking behaviour on digital platforms. Negative and controversial news sometimes actually makes a brand increase in popularity. This phenomenon is known as the Streisand Effect. With a sample of 358 smartphone users in Indonesia, and utilizing a theory of planned behaviour (TPB) approach, we analyze how digital news content influences consumers’ perceptions and behaviour towards brands, primarily through increased information-seeking behaviour. Partial-Least-Squares Structural Equation Modelling and Importance-Performance Analysis (IMPA) were used to analyze the data. Our findings show a significant correlation between information-seeking behaviour and brand popularity, underscoring the impact of digital news content in shaping individual preferences and behaviours. Positive news, negative news, and controversial news, respectively, have different influences on each relationship. This research contributes to a deeper understanding of the role of media in brand management and offers insights for marketers looking to utilize digital platforms for brand enhancement. Future research could expand our study with additional variables.